The way you do anything is the way you do everything : the why of why your business isn't making more money - Evans, Suzanne (John Wiley & Sons Inc, 2014)
"While business consultants are having you scour over profit and loss statements, the real truth is businesses don't fail: people quit. [This book] offers a ... look at how business owners fail to commit. Business success is all about mindset, and author Suzanne Evans helps you uncover your goals and blast away the obstacles that are standing in your way. She offers ways to make more money more quickly and eliminate everything that doesn't work"--Amazon.com